Computer Performance Engineering 7th European Performance Engineering Workshop, EPEW 2010, Bertinoro, Italy, September 23-24, 2010. Proceedings - Aldini, Alessandro; Bernardo, Marco; Bononi, Luciano; Cortellessa, Vittorio; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 7th European Performance Engineering Workshop, EPEW 2010, held in Bertinoro, Italy, in September 2010. The 16 revised full papers presented were carefully reviewed and selected from 38 submissions. The papers are organized in topical sections on network and software performance; timed models and model checking; case studies; model solutions and bounds; and compositional analysis.
Invited Papers -- Modeling and Experimenting with Vehicular Congestion for Distributed Advanced Traveler Information Systems -- Application of Advanced Model-Driven Techniques in Performance Engineering -- Network and Software Performance -- A New Markov-Based Mobility Prediction Algorithm for Mobile Networks -- Performance Aware Reconfiguration of Software Systems -- On the Energy-Performance Tradeoff for Parallel Applications -- Timed Models and Model Checking -- A Framework for Relating Timed Transition Systems and Preserving TCTL Model Checking -- Continuous Time and/or Continuous Distributions -- Model Checking Markov Chains Using Krylov Subspace Methods: An Experience Report -- Case Studies -- A Markovian Agent Model for Fire Propagation in Outdoor Environments -- Queueing Network Models for Performance Evaluation of ZigBee-Based WSNs -- Performance Modeling and Analysis of the Universal Control Hub -- Model Solutions and Bounds -- Accurate Performance Estimation for Stochastic Marked Graphs by Bottleneck Regrowing -- A Numerical Algorithm for the Solution of Product-Form Models with Infinite State Spaces -- State-Dependent Rates and Semi-Product-Form via the Reversed Process -- Compositional Analysis -- Predictive Modelling of Peer-to-Peer Event-Driven Communication in Component-Based Systems -- A Component-Based Solution Method for Non-ergodic Markov Regenerative Processes -- Compositional Abstraction of PEPA Models for Transient Analysis -- Composing Systems While Preserving Probabilities.
Keywords: Computer science; Computer Communication Networks; Software engineering; Logic design; Information systems; Computer Science; Software Engineering; Computer Communication Networks; Logics and Meanings of Programs; Information Systems Applications (incl.Internet).; Programming Techniques; Programming Languages, Compilers, Interpreters